Effects of foliar application of salicylic acid on physiological and qualitative parameters in differently colored Swiss chard (Beta vulgaris L. ssp. cicla) under an aquaponic system - María Carmen Piñero; Jacinta Collado-González; Ginés Otálora; Josefa López-Marín; Francisco M. del Amor (Journal of Agriculture and Food Research, 2025)
The aquaponics technique helps reduce pollution from the discharge of nutrients found in fish waste, while promoting vegetable production. Salicylic acid (SA) plays an essential role in regulating various physiological processes, and its use in combination with aquaponics systems could be a beneficial strategy to enhance the plants' ability to absorb available nutrients. Therefore, we investigated the effect of three irrigation strategies and the foliar application of SA on Swiss chard (Beta vulgaris L.). The results indicated that the white chard variety responded best to the applied treatments. The 50/100 + SA treatment, which consisted of watering for two consecutive days with a mixture of 50 % fish water and drainage, followed by one day with a control solution (traditional irrigation), yielded chard with greater weight, higher total phenolic content, and lower lipid peroxidation. In contrast, the red chard variety showed poor tolerance to the applied dose of salicylic acid.